HARGA, PROMOSI, DAN KUALITAS PELAYANAN SEBAGAI ANTESEDEN KEPUASAN PELANGGAN YANG DI MEDIASAI OLEH KEPUTUSAN MENGGUNAKAN OJEK ONLINE DI YOGYAKARTA - Taufiq Hidayat; Sukardi Sukardi (Universitas Ahmad Dahlan, 2019)
Customer satisfaction is an asset for the company to be a benchmark for the company's success in serving customers. Since its establishment in 2010, GOJEK has consistently served the community, presenting efficient and effective transportation to the Indonesian people spread across several cities. By maintaining the values of a friendly Indonesian character. The population in this study were GO-JEK users. While the sample in this study is GO-JEK users more than once in the city of Yogyakarta. The sampling technique uses a non-probability sampling method. While the data used in this study are primary data by obtaining the data needed by using information techniques, namely by distributing questionnaires. The analysis tool uses multiple linear regression, and doing a partial test knowing whether the independent variables individually have a significant effect on the dependent variable, do the r-test to measure the ability of the model to explain the ability of the dependent variable.The results of the analysis can be concluded that: Price does not have a positive effect on user decisions. Promotion does not have a positive effect on user decisions. Service quality does not have a positive effect on user decisions. User decisions have a positive effect on customer satisfaction. User decisions do not mediate between Price, Promotion and Quality of Service.